(untitled) (World Economics and Finance Bulletin, 2025)
As an inevitable and fundamental result of the globalization of capital markets, developments in the business environment and technological developments that have increased the need for harmonized accounting standards at the global level, many studies, research and professional institutions concerned with the accounting and auditing profession at the global level have confirmed that the international financial reporting standards set by the International Accounting and Financial Reporting Standards Board (IASB) are actually providing financial data that are consistent at the global level. In this article, the researcher seeks to review some of the literature and previous studies that dealt with the adoption of international financial reporting standards at the level of Iraq, taking into account that not all studies in this field can be reviewed, but the article will be limited to some relatively recent studies